Modification and adaptation of the oestrus-ovulation synchronization technics in the hostein-friz cows for shortening anoestrus period and calving interval - Ty, Le Van; Thang, Nguyen Viet; Son, Hoang Nghia; Hung, Nguyen Mong (Academia Journal of Biology, 2014)
Five modifications of the treatment with PGF2α and GnRH for oestrus synchronization in dairy cows have been tested and compared. High percentage of cows became oestrus synchronized with ovulation and high concepted rate after IA was recorded in the cows, received 2 injections of PGF2 (2 ml) mixed with GnRH (10mg ) with interval 7 days apart. Application of this treatment for 65 post-partum dairy cows immediately a month after calving, reduced the interval between the parturition and the conception to 91 ± 28 days against 214 ± 152 days in the case of routine oestrus detection and IA. So treatment with 2 injections of PGF2α mixed with GnRH not only made oestrus detection more feasible but could be used for shortening the length between two parturition in cows.